Prevalence, determinants and clinical correlates of vitamin D deficiency in adults with inhaled corticosteroid-treated asthma in London, UK. Issue 175 (January 2018) - Jolliffe, David A.; Kilpin, Kate; MacLaughlin, Beverley D.; Greiller, Claire L.; Hooper, Richard L.; Barnes, Neil C.; Timms, Peter M.; Rajakulasingam, Raj K.; Bhowmik, Angshu; Choudhury, Aklak B.; Simcock, David E.; Hyppönen, Elina; et al.
Highlights: Vitamin D deficiency is common among UK adults with ICS-treated asthma. Classical environmental determinants of vitamin D status operate in this population. Vitamin D status did not associate with markers of asthma severity or control. Genetic variation in the vitamin D pathway did not influence vitamin D status or measures of asthma severity or control. Abstract: Vitamin D deficiency is common in children with asthma, and it associates with poor asthma control, reduced forced expiratory volume in one second (FEV1 ) and increased requirement for inhaled corticosteroids (ICS). Cross-sectional studies investigating the prevalence, determinants and clinical correlates of vitamin D deficiency in adults with asthma are lacking. We conducted a multi-centre cross-sectional study in 297 adults with a medical record diagnosis of ICS-treated asthma living in London, UK. Details of potential environmental determinants of vitamin D status, asthma control and medication use were collected by questionnaire; blood samples were taken for analysis of serum 25(OH)D concentration and DNA extraction, and participants underwent measurement of weight, height and fractional exhaled nitric oxide concentration (FeNO), spirometry and sputum induction for determination of lower airway eosinophil counts (n = 35 sub-group). Thirty-five single nucleotide polymorphisms (SNP) in 11 vitamin D pathway genes ( DBP, DHCR7, RXRA, CYP2R1, CYP27B1, CYP24A1, CYP3A4 CYP27A1, LRP2, CUBN, VDR ) were typed using Taqman allelic discrimination assays. Linear regression was used to identify environmental and genetic factors independently associated with serum 25(OH)D concentration, and to determine whether vitamin D status was independently associated with Asthma Control Test (ACT) score, ICS dose, FeNO, forced vital capacity (FVC), FEV1 or lower airway eosinophilia. Mean serum 25(OH)D concentration was 50.6 nmol/L (SD 24.9); 162/297 (54.5%) participants were vitamin D deficient (serum 25(OH)D concentration <50 nmol/L). Lower vitamin D status was associated with higher body mass index (P = 0.014), non-White ethnicity (P = 0.036), unemployment (P for trend = 0.012), lack of vitamin D supplement use (P < 0.001), sampling in Winter or Spring (P for trend <0.001) and lack of a recent sunny holiday abroad (P = 0.030), but not with potential genetic determinants. Vitamin D status was not found to associate with any marker of asthma control investigated. Vitamin D deficiency is common among UK adults with ICS-treated asthma, and classical environmental determinants of serum 25(OH)D operate in this population. However, in contrast to studies conducted in children, we found no association between vitamin D status and markers of asthma severity or control.